2022
DOI: 10.1002/prp2.917
|View full text |Cite
|
Sign up to set email alerts
|

The interacting physiology of COVID‐19 and the renin‐angiotensin‐aldosterone system: Key agents for treatment

Abstract: SARS‐CoV‐2 interacting with its receptor, angiotensin‐converting enzyme 2 (ACE2), turns the host response to viral infection into a dysregulated uncontrolled inflammatory response. This is because ACE2 limits the production of the peptide angiotensin II (Ang II) and SARS‐CoV‐2, through the destruction of ACE2, allows the uncontrolled production of Ang II. Recovery from trauma requires activation of both a tissue response to injury and activation of a whole‐body response to maintain tissue perfusion. Tissue and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 103 publications
(202 reference statements)
0
40
0
Order By: Relevance
“…Alternately or additionally, the loss of ACE-2 enzyme activity and reduced synthesis of angiotensin 1-7 causes elevated levels of angiotensin 1-8 that binds to AT1 receptors on cells and this is also known to activate the NLRP3 inflammasome to cause cell death by pyroptosis in lung epithelium cells, endothelium, and cardiomyocytes. 30,31 These important findings of NLRP3 inflammasome and renin-angiotensin system (RAS) activation give a and cellular explanation for the proinflammatory cytokine storm and acute multi-organ failures widely reported in patients with severe COVID-19 infection as well as future directions for discovering drug candidates to block activation of the NLRP3 inflammasome (reviewed by Lumbers et al 32 ). But do they explain "LONG COVID" and suggest drug treatments, appropriate doses, and administration timing for this puzzling disorder?…”
Section: Hyp Othe S Ismentioning
confidence: 99%
See 1 more Smart Citation
“…Alternately or additionally, the loss of ACE-2 enzyme activity and reduced synthesis of angiotensin 1-7 causes elevated levels of angiotensin 1-8 that binds to AT1 receptors on cells and this is also known to activate the NLRP3 inflammasome to cause cell death by pyroptosis in lung epithelium cells, endothelium, and cardiomyocytes. 30,31 These important findings of NLRP3 inflammasome and renin-angiotensin system (RAS) activation give a and cellular explanation for the proinflammatory cytokine storm and acute multi-organ failures widely reported in patients with severe COVID-19 infection as well as future directions for discovering drug candidates to block activation of the NLRP3 inflammasome (reviewed by Lumbers et al 32 ). But do they explain "LONG COVID" and suggest drug treatments, appropriate doses, and administration timing for this puzzling disorder?…”
Section: Hyp Othe S Ismentioning
confidence: 99%
“…As outlined by Head et al in this Journal 37 in many people, SARS‐CoV‐2 reaches the lungs causing an acute respiratory distress (ARDS) because the virus has a lethal action on infected alveoli that impairs oxygenation of blood. The virus then crosses the alveoli–blood barrier and because of the widespread cellular distribution of its target ACE‐2 results in other organs such as heart, liver, kidney, and CNS becoming infected, provoking an immune response and organ failure, covered in Lumbers et al 32 This can be fatal particularly in elderly adults with comorbidities such as hypertension, type 2 diabetes, and obesity 4 . The United States among others have reported that young adults with obesity are more likely to require hospitalization and develop more severe disease than non‐obese young adults, 6 consistent with the known increased distribution and activity of the renin–angiotensin system in obesity 38 .…”
Section: Actions Of Sars‐cov‐2mentioning
confidence: 99%
“…In fact, as outlined by Lumbers et al in this Themed Review 5 it is critical in understanding the pathogenesis of COVID‐19 to be aware of the destruction of the ACE2 receptor induced by SARS‐CoV‐ 2 binding. ACE2 is a component of the renin–angiotensin system (RAS) which is classically viewed as a circulating endocrine system which through the actions of its major peptide, angiotensin II (Ang II) controls blood pressure and fluid and electrolyte homeostasis.…”
mentioning
confidence: 99%
“…In contrast, lower respiratory tract infection does not favor SARS‐CoV‐2 self‐assembly at scale but critically drives COVID‐19 pathophysiology. It is this pathophysiology that is thoroughly explored by Lumbers et al 5 in their sequenced review.…”
mentioning
confidence: 99%
See 1 more Smart Citation